Measuring the elastic tensor of a monolithic SiC hollow cylinder with resonant ultrasound spectroscopy. (January 2019) - Donahue, Carly M.; Remillieux, Marcel C.; Singh, Gyanender; Ulrich, T.J.; Migliori, Robert J.; Saleh, Tarik A.
Abstract: Resonant Ultrasound Spectroscopy (RUS) has become a standard tool in material science to measure nondestructively the elastic properties of materials. The widespread adoption of this tool for applications related to nondestructive testing and structural health monitoring in the industry and other places has been restricted thus far by some requirements imposed by RUS on the sample to be tested, in particular the fact that the sample geometry should be relatively simple (e.g., cuboid, cylinder, or sphere). In this paper, we use RUS to determine the baseline material properties of a hollow cylinder made of monolithic SiC, a surrogate material and geometry representing nuclear fuel cladding for this study. Typically, elastic properties of the nuclear fuel cladding samples are inspected destructively (e.g., indentation) or with acoustic techniquesrequiring multiple and cumbersome measurements. Here, a relatively new RUS approach specifically developed to measure the elastic tensor of samples with arbitrary geometries is used. The results obtained from this RUS approach are compared to values reported in the literature. As a second verification step, vibrational mode shapes computed numerically with the elastic constants are compared to those measured on the sample using a 3D laser Doppler vibrometer, showing an excellent agreement.